2017
DOI: 10.1667/rr14558.1
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Radiation Responsive Proteins to Predict Radiation Exposure in Total-Body Irradiation and Partial-Body Irradiation Models

Abstract: In the event of a radiological or nuclear attack, advanced clinical countermeasures are needed for screening and medical management of the exposed population. In such a scenario, minimally invasive biomarkers that can accurately quantify radiation exposure would be useful for triage management by first responders. In this murine study, we evaluated the efficacy of a novel combination of radiation responsive proteins, Flt3 ligand (FL), serum amyloid A (SAA), matrix metalloproteinase 9 (MMP9), fibrinogen beta (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 17 publications
0
28
1
Order By: Relevance
“…The proteins responding to irradiation in both directly irradiated and bystander animals were acute-phase proteins (PTX-3 and lipocalin-2) (Mantovani et al 2003;Pixley and Stanley 2004;Asimakopoulou, Borkham-Kamphorst, et al 2016;, growth factors involved in stress response (M-CSF) (Pixley and Stanley 2004) or chemokines (CXCL16), indicating that cellular stress induced by ionizing radiation was transmitted by EVs to bystander mice as well. All of these proteins were already shown to be altered by radiation and various forms of oxidative stress (Haglund et al 2008;Matsumura and Demaria 2010;Shiraki et al 2012;Ariyoshi et al 2014;Tomandlova et al 2015;Isik Balci et al 2016;Yoon et al 2016;Sproull et al 2017). Two of the above four proteins were reported to be involved in radiation-induced bystander responses as well.…”
Section: Discussionmentioning
confidence: 97%
“…The proteins responding to irradiation in both directly irradiated and bystander animals were acute-phase proteins (PTX-3 and lipocalin-2) (Mantovani et al 2003;Pixley and Stanley 2004;Asimakopoulou, Borkham-Kamphorst, et al 2016;, growth factors involved in stress response (M-CSF) (Pixley and Stanley 2004) or chemokines (CXCL16), indicating that cellular stress induced by ionizing radiation was transmitted by EVs to bystander mice as well. All of these proteins were already shown to be altered by radiation and various forms of oxidative stress (Haglund et al 2008;Matsumura and Demaria 2010;Shiraki et al 2012;Ariyoshi et al 2014;Tomandlova et al 2015;Isik Balci et al 2016;Yoon et al 2016;Sproull et al 2017). Two of the above four proteins were reported to be involved in radiation-induced bystander responses as well.…”
Section: Discussionmentioning
confidence: 97%
“…Our results (Table 2 and Supplementary Table S4 ) showed that combinations of FDXR, DDB2 and ACTN1 proteins generate an accurate prediction of the radiation dose in human lymphocytes in vivo : their mean absolute errors were ≤0.13 Gy over the tested dose range of 0 to 2 Gy. Previous studies have similarly used a combinatorial approach of plasma protein markers to provide an improved dose assessment compared to a single biomarker alone in mouse 10 and NHP models 13 . Budworth et al .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have systematically validated radio-responsive human protein markers in vivo for dose- and time-response after radiation exposure. Radiation responsive plasma proteins such as Flt3 ligand (Flt3L), serum amyloid A (SAA) and Interleukin-6 (IL-6) have been studied in mouse models as markers of acute radiation syndrome and radiation exposure up to a week 10 , 11 . Using the NHP model, C-reactive protein (CRP), SAA, IL-6, Flt3L protein biomarkers expressed in NHP plasma have been proposed as early indicators of dose assessment and radiation-induced injury up to ~7 days post irradiation 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Though many of the early radiation dose prediction models were based on uniform total body exposure, new research in the field is directed at developing dose prediction models for partial exposures, in addition to organ-specific markers of radiation damage. 50,51 These models are expected to be more relevant to radiological event scenarios, and identification of organ-specific markers of radiation damage will enhance medical management of radiation accident victims.…”
Section: Sproull Et Almentioning
confidence: 99%
“…Note: Rankings are based on complexity of the model studied (in vitro, murine, non-human primate, or human clinical study), their current level of technological deployment capability, and level of advancement in the basic research. 50 operational throughput capacity, and phase of development. Cytogenetic assessment and lymphocyte kinetics/ clinical exam are rated as deployment-ready, though these technologies are not yet available at surge capacity levels.…”
Section: Current State Of the Sciencementioning
confidence: 99%